Analysis of Students' Learning Style Profiles in 5th Grade Differentiate Learning in Elementary School - Fiky Herdianto; Mudzanatun Mudzanatun; Sri Suneki; Diyah Rahayu Tunjungsari (research, training and philanthropy institution Natural Aceh, 2023)
Students have characteristics in understanding the ability to understand and obtain different information. The purpose of this study was to find out the results of the description of the learning style profile of fifth-grade students at SD Negeri Pandeanlamper 01 Semarang City. This method uses a qualitative descriptive approach. The research strategy used was observation sheets by distributing questionnaires based on learning styles, visual, auditory, and kinesthetic. Based on the results of the study, it was shown that fifth-grade students at SD Negeri Pandeanlamper 01 were more dominant with a visual learning style, obtaining a percentage of 46.63%. This indicates that most students better understand information with their sense of sight, such as seeing pictures and learning video animations. Next is the kinesthetic learning style of 28.67% by processing physical and mental information to move, and the auditory learning style of 25.00% by gaining understanding by listening. This learning style facilitates the needs of diverse students in differentiated learning. Learning style profiles in differentiated learning provide learning readiness, interests, and things each student likes. With differentiated learning, all the needs of students can be accommodated according to each student's interests and learning profile.